2011
DOI: 10.1523/jneurosci.3235-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Activating Voltage- and Calcium-Dependent Potassium (BK) Conductance Promotes Bursting in Pituitary Cells: A Dynamic Clamp Study

Abstract: The electrical activity pattern of endocrine pituitary cells regulates their basal secretion level. Rat somatotrophs and lactotrophs exhibit spontaneous bursting and have high basal levels of hormone secretion, while gonadotrophs exhibit spontaneous spiking and have low basal hormone secretion. It has been proposed that the difference in electrical activity between bursting somatotrophs and spiking gonadotrophs is due to the presence of large conductance potassium (BK) channels on somatotrophs but not on gonad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(129 citation statements)
references
References 44 publications
3
124
2
Order By: Relevance
“…We have shown that bursting can be rescued by adding BK current back to the cell using the dynamic clamp technique (here and in Ref. 34). In Fig.…”
Section: Bursting Superiority Depends On the Frequency Of Spikingmentioning
confidence: 91%
“…We have shown that bursting can be rescued by adding BK current back to the cell using the dynamic clamp technique (here and in Ref. 34). In Fig.…”
Section: Bursting Superiority Depends On the Frequency Of Spikingmentioning
confidence: 91%
“…This prediction was tested experimentally and validated. 10 In summary, the different fast/slow decompositions tell us useful information about a model cell's dynamics, and with the dynamic clamp technique, often in combination with pharmacological agents, these model predictions can be and have been tested.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Bursting activity is characterized by alternation between periods of spiking and periods of rest, and is driven by slow variations in one or more slowly changing variables, such as the intracellular calcium concentration. Bursting oscillations are often more efficient than tonic spiking in mediating the release of neurotransmitter or hormone.…”
Section: Introductionmentioning
confidence: 99%
“…The reciprocal conversion is also true: addition of an artificial BK conductance to cultured gonadotrophs through the dynamic clamp technique changes their activity pattern from spiking to bursting. 19 Mathematical modeling predicted that the activation time constant of the BK conductance is important. BK activation must be fast to promote bursting; if too slow, then the BK current does not promote bursting and instead takes on its traditional inhibitory role on electrical activity.…”
Section: P0185mentioning
confidence: 99%
“…BK activation must be fast to promote bursting; if too slow, then the BK current does not promote bursting and instead takes on its traditional inhibitory role on electrical activity. 19 Faster BK activation kinetics limit spike amplitude, preventing full activation of the repolarizing delayed rectifier K 1 current, so membrane potential weakly oscillates around a depolarized level 14,22,23 before falling back toward rest, which results in bursting, increased Ca 21 influx and global Ca 21 signals.…”
Section: P0185mentioning
confidence: 99%